The Importance of Design Thinking for Students Majoring in Art and Design in Vocational Colleges - Zhou, Zhonggong; Jeong, Dubae (Journal of Educational Research and Policies, 2024)
The cultivation of design thinking ability among students majoring in art and design in vocational colleges is related to the implementation of national innovation and development strategies and the cultivation of high-skilled talent. This study focuses on the problems of lagging educational concepts, weak cultural foundations, and insufficient artistic literacy in the cultivation of creative thinking among students majoring in art and design in vocational colleges. This study explores effective ways to enhance the design thinking ability of students majoring in art and design in vocational colleges. Research has shown that current vocational art and design education generally suffers from problems such as emphasizing skills over creativity, theory over practice, and a lack of systematic training in innovative thinking. This results in students lacking independent innovation ability and the ability to solve practical design problems, leading to insufficient employment competitiveness for graduates. This study focuses on students majoring in art and design in vocational colleges and conducts an in-depth analysis of the factors that affect the cultivation of design thinking among students majoring in art and design in vocational colleges. The research results indicate that improving the design thinking ability of art and design majors in vocational colleges requires the following steps. First, it is necessary to update educational concepts; integrate design thinking into various aspects of teaching; change the traditional exam-oriented education model; and focus on cultivating students' critical thinking, systematic thinking, and innovative thinking. Second, it is necessary to strengthen the teaching of basic courses, consolidate students' professional foundation, cultivate their aesthetic ability and artistic cultivation, and lay a solid foundation for the cultivation of design thinking. Again, innovative teaching methods, such as project-based learning, case-based teaching, and studio teaching, are needed to stimulate students' interest in learning and improve their learning enthusiasm. At the same time, practical teaching should be strengthened to increase students' opportunities to participate in practical projects, allowing them to learn and enhance their design thinking abilities through practice. In addition, it is necessary to strengthen school enterprise cooperation, establish an integrated teaching model of industry university research, provide more internship and employment opportunities for students, and cultivate their professional qualities and innovation abilities. Finally, it is necessary to create a good campus cultural atmosphere, encourage students to actively participate in innovation and entrepreneurship activities, and cultivate their innovative spirit and entrepreneurial ability.